Improved Drilling Accuracy Results in Reduced Ore Dilution at Evolution, Cracow - Phil Jones; Ben Johnson (International Society of Explosives Engineers, 2019)
During a period of six months in FY2018, a series of trials were conducted to compare drilling accuracy using two different methodologies and the subsequent impact this had on ore dilution. Testing was conducted at Cracow underground gold mine in Queensland, Australia. The drill rig’s existing alignment process was compared to a new technology system with the following observations: